Vulnerabilidade externa no Brasil: ensaios sobre fluxos internacionais de capitais, instabilidade financeira e controle de capitais - Vanessa da Costa Val Munhoz (2010)
The general objective of this dissertation is to examine the relationship between the external vulnerability in Brazil and the volatility of international capital flows. More specifically, the research is organized into three questions: to what extent and how strongly are the financial instability and macroeconomic performance in developing countries associated with the financial liberalization process and with the volatility of foreign capital flows? Are there any different impacts on the Brazilian external vulnerability when we are dealing with capital flight or volatility of capital flows? Does the empirical analysis of the relationship between the volatile movements of financial flows and macroeconomic stability in developing countries suggest the introduction of permanent capital controls? The study is composed of three interrelated essays. The theoretical and empirical analysis developed in Essay 1 shows that the growing process of liberalization of financial flows generated a large attraction of unstable financial flows. An improvement in economic fundamentals is not sufficient to avert the instability of the financial market, given the continuous attraction of capital flow into the Brazilian economy and the consequent increase in the potential for financial fragility. Essay 2 suggests that the volatility indicator for financial flows and the measures of capital flight are complementary. While the first indicator captures moments when Brazil is facing a period of capital inflows and the transition to sharp reversals and large negative transfers, the capital flight indicates the sensitivity of capital flows toward Brazil due to unstable factors and external shocks. Finally, Essay 3 uses an econometric panel data and shows a clear difference in the pattern of the relationship between capital flows versus exchange rate and capital flows versus interest rate in countries that have adopted restrictive measures to control speculative capital. The negative macroeconomic impact of unrestricted financial flows, such as high exchange volatility and loss of autonomy of monetary policy, justify and support the implementation of a comprehensive set of capital controls on a permanent basis. Indeed, the absence of permanent controls on capital inflows hinders the sustainable economic development in Brazil.